Agricultural Supply Chain Risk Assessment in the Caribbean - Arias Carballo, Diego (World Bank, Washington, DC, 2014)
A rapid agricultural supply chain risk assessment, recently developed by the World Bank, constitutes a useful tool for a system-wide approach to identify risks, risk exposure, the severity of potential loses, and options for risk management either by supply chain participants (individually or collectively) or by third parties (government). Supply chain risk management is the systematic process of managing the most damaging events that can negatively affect the supply chain, and their likely incidence and impact(s). The proposed unit of analysis for risk and risk management assessment is the supply chain, logistics and communications are embedded in all these flows, and poor logistics and communications are often a major source of risk facing an agricultural supply chain. The agri-food system also includes farmers and a diverse range of firms, including backward-linked input suppliers and forward-linked intermediaries, processors, exporters, wholesalers, and retailers.